Nucleopolyhedrosis Virus of Spodoptera Utura: Influence of Environmental Factors on Efficacy And Improvement for Field Application - Abdul Bakir, Mohammad (2001)
Chemical pesticides significantly reduce agricultural losses but pose environmental hazards. Their effectiveness are threatened by increasing insect resistance and unwanted destruction of non-target organisms. Nucleopolyhedroviruses (NPVs) are getting wide attention as an alternative and biorational method to control insect pests. In this study, infectivity of a locally isolated NPV to control the polyphagous pest Spodoptera litura (Fabricius) (Lepidoptera: Noctuidae) was examined. The effects of different environmental factors such as pH, temperature, sunlight and ultraviolet lights (UVA, UV-B and UV-C) on the infectivity of the virus were studied. Capabilities of different materials to protect the virus from deleterious effects of UV and sunlight were evaluated. The virus was formulated with different protectant materials and the effectiveness of different virus formulations at practical field level with single and multiple applications to control S. litura were investigated.